Effectiveness and cost-effectiveness of community singing on mental health-related quality of life of older people: Randomised controlled trial. (September 2015) - Coulton, Simon; Clift, Stephen; Skingley, Ann; Rodriguez, John
Abstract : Background: As the population ages, older people account for a greater proportion of the health and social care budget. Whereas some research has been conducted on the use of music therapy for specific clinical populations, little rigorous research has been conducted looking at the value of community singing on the mental health-related quality of life of older people. Aims: To evaluate the effectiveness and cost-effectiveness of community group singing for a population of older people in England. Method: A pilot pragmatic individual randomised controlled trial comparing group singing with usual activities in those aged 60 years or more. Results: A total of 258 participants were recruited across five centres in East Kent. At 6 months post-randomisation, significant differences were observed in terms of mental health-related quality of life measured using the SF12 (mean difference = 2.35; 95% CI = 0.06–4.76) in favour of group singing. In addition, the intervention was found to be marginally more cost-effective than usual activities. At 3 months, significant differences were observed for the mental health components of quality of life (mean difference = 4.77; 2.53–7.01), anxiety (mean difference =–1.78; –2.5 to –1.06) and depression (mean difference =–1.52; –2.13 to –0.92). Conclusions: Community group singing appears to have a significant effect on mental health-related quality of life, anxiety and depression, and it may be a useful intervention to maintain and enhance the mental health of older people.